Efektivitas Penggunaan Aplikasi Microsoft Team For Education Siswa Dalam Pembelajaran Daring Selama Pandemi Covid 19: Defi Pujianto (Universitas Mahakarya Asia, 2021)
Until now, the covid-19 pandemic, it is not known when it will end. Meanwhile, student learning activities must be carried out. Learning through online is a method that allows it to be carried out on students. Currently, online methods are also being developed to support the student learning process. The online learning method is considered to be more effective and efficient. The effectiveness of online learning relies on several factors, namely the application used, discipline in learning and the method of delivering learning materials. With a low cost but being able to use application features to support the online learning model, it can be said to be efficient. The Microsoft Team for Education application is an application designed specifically for education. The purpose of this study was to determine the effectiveness of using the Microsoft Team for Education application in online learning during the covid 19 pandemic. This research method used qualitative methods and distributed questionnaires to students. From the results of the questionnaire, it was found that the results of the attention aspect resulted in a percentage value of 54%, the material delivery aspect resulted in a 39% percentage value, the assignment assignment and learning assessment aspects got a 49% percentage value, the student and lecturer interaction aspects received a 57% percentage value and the student learning motivation aspect get a percentage value of 52%. These aspects have good criteria. for aspects with sufficient criteria in the aspect of participating in learning courses with a percentage value of 32%. Keywords: Covid 19, Effective, Microsoft team For Education Reference 365, T. O. (2020, maret 20). Menggunakan Microsoft Teams untuk Kelas Online (Remote ). pp. https://365.telkomuniversity.ac.id/menggunakan-microsoft-teams-untuk-kelas-online-remote-learning/. Ade Rahma Gusti, Y. A. (2020). Penilaian Afektif Pembelajaran Daring IPA Terpadu Dengan Menggunakan Media Whatsapp. Journal for Physics Education and Applied Physic, 2(2), 65. microsoft. (2021, july 15). Microsoft. (Microsoft) Retrieved july 15, 2021, from https://www.microsoft.com/id-id/education/products/teams Muljono, D. &. (2008). Pengukuran Dalam Bidang Pendidikan. Jakarta: PT Grasindo. Satuan Tugas Penanganan COVID-19. (2021, June 9). https://covid19.go.id/. (https://covid19.go.id/) Retrieved june 2021, 2021, from https://covid19.go.id/ Sudjana, N. (2004). In Dasar-dasar Proses Belajar Mengajar. Bandung: Sinar Baru Algensindo Offset.